Long-Term Responders After Autologous Stem Cell Transplantation in Multiple Myeloma - Oliver-Caldes, Aina; Soler-Perromat, Juan Carlos; Lozano, Ester; Moreno, David; Bataller, Alex; Mozas, Pablo; Garrote, Marta; Setoain, Xavier; Aróstegui, Juan Ignacio; Yagüe, Jordi; Tovar, Natalia; Jiménez, Raquel; et al. (Frontiers in Oncology, 2022)
Multiple myeloma (MM) is considered an incurable hematological neoplasm. For transplant-eligible patients, initial treatment includes an induction phase followed by an autologous stem cell transplantation (ASCT). Despite the introduction of several drugs in the past years, relapses still occur. Nevertheless, some patients achieve sustained responses after successful induction treatment and ASCT. We retrospectively evaluated all patients diagnosed with MM in our institution who underwent induction treatment and ASCT between 1990 and 2015. The subset of patients who achieved a sustained response (any degree) for 5 or more years after ASCT without further treatment or signs of progression were distinguished as “long-term responders” (LTR). In the non-LTR group, a cohort referred as “prolonged responders” (PLR) showed sustained response of at least 5 years after ASCT but eventually relapsed. We collected and analyzed clinical and laboratory data. Two hundred and fifty patients were diagnosed with MM and received induction treatment and ASCT at our institution in the study period. Among them, 54 (21.6%) patients met the criteria for LTR. Some diagnostic features such as a younger age, female gender, ECOG performance status of 0, lower International Staging System (ISS) stage, lower bone marrow plasma cell infiltration and lower serum levels of calcium, C-reactive protein and lactate dehydrogenase (LDH) were found to be more prevalent in LTR. Female gender, an ECOG performance status of 0, a localized Durie-Salmon stage, an ISS of I-II, the absence of bone disease and an LDH within normal range were also predictive of longer progression-free survival (PFS) and overall survival (OS) in the whole cohort. The depth of the response achieved after induction and ASCT as well as the administration of an IMID-based maintenance regimen may play a role in the differences observed on PFS between cohorts. A detectable M-protein with a monoclonal gammopathy of undetermined significance (MGUS)-like behavior was detected in one third of LTR after ASCT. Although relapses keep occurring in patients who achieve a 5-year treatment-free period after ASCT, a plateau is observed in the survival curves at approximately 21 years of follow-up.